Role of lipid phosphate phosphatase 3 in human aortic endothelial cell function - Touat-Hamici, Zahia; Weidmann, Henri; Blum, Yuna; Proust, Carole; Durand, Hervé; Iannacci, Francesca; Codoni, Veronica; Gaignard, Pauline; Thérond, Patrice; Civelek, Mete; Karabina, Sonia A.; Lusis, Aldons J.; et al. (Cardiovascular research, 2016)
Lipid phosphate phosphatase 3; type 2 phosphatidic acid phosphatase β (LPP3; PPAP2B) is a transmembrane protein dephosphorylating and thereby terminating signalling of lipid substrates including lysophosphatidic acid (LPA) and sphingosine-1-phosphate (S1P). Human LPP3 possesses a cell adhesion motif that allows interaction with integrins. A polymorphism (rs17114036) in PPAP2B is associated with coronary artery disease, which prompted us to investigate the possible role of LPP3 in human endothelial dysfunction, a condition promoting atherosclerosis. To study the role of LPP3 in endothelial cells we used human primary aortic endothelial cells (HAECs) in which LPP3 was silenced or overexpressed using either wild type or mutated cDNA constructs. LPP3 silencing in HAECs enhanced secretion of inflammatory cytokines, leucocyte adhesion, cell survival, and migration and impaired angiogenesis, whereas wild-type LPP3 overexpression reversed these effects and induced apoptosis. We also demonstrated that LPP3 expression was negatively correlated with vascular endothelial growth factor expression. Mutations in either the catalytic or the arginine-glycine-aspartate (RGD) domains impaired endothelial cell function and pharmacological inhibition of S1P or LPA restored it. LPA was not secreted in HAECs under silencing or overexpressing LPP3. However, the intra- and extra-cellular levels of S1P tended to be correlated with LPP3 expression, indicating that S1P is probably degraded by LPP3. We demonstrated that LPP3 is a negative regulator of inflammatory cytokines, leucocyte adhesion, cell survival, and migration in HAECs, suggesting a protective role of LPP3 against endothelial dysfunction in humans. Both the catalytic and the RGD functional domains were involved and S1P, but not LPA, might be the endogenous substrate of LPP3.